2015
DOI: 10.1177/2047173416630012
|View full text |Cite
|
Sign up to set email alerts
|

The quality of high school students’ problem solving from an expertise development perspective

Abstract: The ability to solve problems is a key skill and is essential to our day-today lives, at home, at school and at work. The present study explores the quality of managerial problem-solving of participants who are in secondary education. We studied 10th, 11th, and 12th graders following a business track in the Netherlands. Participants were asked to represent, diagnose and solve business cases. The transcripts (handwritten 'case solutions') of all 213 participants were analysed for managerial knowledge and proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Evaluating and processing data can yield an accurate depiction of the situation. Students who are adept in identifying problems demonstrate a greater comprehension of the problems [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating and processing data can yield an accurate depiction of the situation. Students who are adept in identifying problems demonstrate a greater comprehension of the problems [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Extending the solution is a multi-stage process in which the good and negative features of various solutions are weighed and merged to determine the overall solution [45]. Elvira et al [36] discovered the real problem solvers would evaluate potential solutions twice as often as beginners when examining a case. Celik et al [46] found that students assess the adequacy of a solution by reviewing the effectiveness of the chosen problem-solving technique.…”
Section: Discussionmentioning
confidence: 99%
“…Working for the solution is expected not to be much harder and will consume lesser time. Indeed, it seems that when learners are familiar with a problem or some aspects of a problem [36], [37] helps to create a bridge between the problem and the solution which later improves their P-S abilities [38], [39].…”
Section: Research Questionmentioning
confidence: 99%
“…During the learning process, to overcome the gap between experts and beginners, lecturers can provide guidance for beginners Experts tend to work systematically from problem statement to answer because they can easily execute their solution plan. Instead, the novice must develop a solution plan, sometimes through a process of means-goal analysis (Elvira et al, 2015).…”
Section: Example Of Problem Formulation Translatementioning
confidence: 99%
“…During the learning process, to overcome the gap between experts and beginners, lecturers can provide guidance for beginners Experts tend to work systematically from problem statement to answer because they can easily execute their solution plan. Instead, the novice must develop a solution plan, sometimes through a process of means-goal analysis(Elvira et al, 2015).The last indicator is the ability to make and determine conclusions. This indicator is in the good category which means that students can make conclusions correctly based on the solutions that have been found when solving problems.…”
mentioning
confidence: 99%